Servo-Controlled 5-Axis 3D Printer from an Open-Source Kit - Corpuz, Dawn Christine P (Archīum Ateneo, 2019)
3D printers can serve as a remarkable tool for rapid prototyping of items due to its relatively low cost of materials and operation, which makes it more accessible to the public, and its being easier to use to print objects. However, some designs cannot easily be printed due to overhanging parts and thus require support structures to be printed. This leads to wasted material and more time spent due to having to print these support structures. Thus, as a solution to this problem, this paper proposes a 5-axis 3D printer design that uses servomotors to give 3-axis 3D printers the additional rotational axes, which can lessen printing time and can print overhanging structures without any additional support. From one test print that used 29 grams of material with support, the trials show a reduction of 7 grams of material using the 5-axis system. However, the print time increased by 1 h and 35 min due to the slow z movement of the printer.